2023
DOI: 10.1007/s11678-022-00723-7
|View full text |Cite
|
Sign up to set email alerts
|

Frakturfolge Typ 2 des proximalen Humerus – klinische Ergebnisse nach endoprothetischer Therapie

Abstract: Fracture sequelae type 2 of the proximal humerus-clinical results after arthroplastyLocked dislocations of the glenohumeral joint are rare but often painful and are associated with limited range of motion in the shoulder. In patients of advanced age, arthroplasty is increasingly indicated as a surgical treatment option. Preoperatively, the direction of dislocation, the presence and extent of a glenoid defect, and the soft tissue situation (rotator cuff status, joint capsule) should be analyzed in a differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In type 2a lesions, posterior locked shoulder dislocation is present. Studies by our group showed that glenoid defects are very rarely observed in dorsal dislocation, and treatment with an ASA can achieve better functional results as long as the rotator cuff is intact [ 11 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In type 2a lesions, posterior locked shoulder dislocation is present. Studies by our group showed that glenoid defects are very rarely observed in dorsal dislocation, and treatment with an ASA can achieve better functional results as long as the rotator cuff is intact [ 11 , 22 ].…”
Section: Discussionmentioning
confidence: 99%